(untitled) (Baghdad Science Journal, 2009)
Proteus mirabilis ? -lactamase of local isolates number 4TF represent karkh side and 20TF represent rusafa side of Baghdad were extracted and purified 23.17, 25.23 fold with yield of 36.66 %, 37.5% and specific activity 11.8, 12.6 of unit/ mg protein by DEAE –cellulose and Sepharose 4B (respectively ).Molecular weight of both enzyme was about 35500 Dalton determined by gel filtration. The study indicated that the isoelectric point of purified ? -lactamase that extracted from isolate number 4TF and 20TF was 5.4.